The evolution of false self-employment in the British construction industry: a neo-Polanyian account of labour market formation - Behling, Felix; Harvey, Mark (Work, Employment & Society, 2015)
Governments in Europe and elsewhere have renewed their attention to the fiscal regulation of their economies in order to close tax loopholes and boost revenues in response to the financial crisis. The article uses a neo-Polanyian ‘instituted economic process’ approach to explore and explain the uniquely high level of bogus self-employment in the UK construction industry, facilitated by confused law and stimulated by a bespoke construction fiscal regime, resulting in endemic tax evasion. It examines how the co-evolution of employment status law and a sector-specific fiscal regime maps tightly onto the emergence of mass self-employment, as evidenced by comparative labour market and sectoral statistics. Seeing competition as an instituted process within these distinctive market arrangements, it identifies a form of ‘degenerative competition’, driving out both genuine direct-employment and self-employment, and driving in bogus self-employment, with its attendant substantial fiscal losses, failed skill reproduction and poor productivity.
Sociology
Keywords: British construction industry; Great Britain; bogus self-employment; business revenue; construction industry; economic sociology; instituted economic process; labour market formation; self-employment; tax evasion; tax loopholes

Ontario's infrastructure boom: a socioecological fix for air pollution, congestion, jobs, and profits - Nugent, James Patrick (Environment & Planning A, 2015)
Infrastructure projects provide a spatial fix by increasing the scale and rate of capital accumulation, and because infrastructure projects themselves absorb massive amounts of productive and finance capital. I seek to explain the timing, character, and consequences of a Can $85 billion infrastructure boom in Canada's largest province, Ontario, between 2003 until 2013. I focus on the expansion and privatization of environmentally oriented infrastructure in Ontario via three policies: the conversion of public coal power plants to private natural gas and nuclear facilities; the Green Energy Act (a renewable energy feed-in tariffs programme); and The Big Move (a Can $50 billion dollar rapid transit plan using a public–private partnership model). I employ a Polanyian– O'Connor approach to emphasize the role of labour, environmental groups, and other social movement groups in bringing these investments about. I argue that infrastructure investments are not only a spatial fix aimed at finding capital a safe long-term investment and addressing class struggles around job creation. In Ontario these infrastructure investments have also provided the state with a broader socioecological fix for the economic and political contradictions stemming from air pollution and congestion. Social movements have pressured the government to address what James O'Connor refers to as the underproduction of the conditions of production: that is, degraded human health and quality of life; a deteriorating environment; and inadequate public infrastructure. Throughout the paper I emphasize how the socioecological fix in Ontario is being accomplished by advancing the neoliberal governance of public infrastructure. I point to how these neoliberal socioecological fixes are simply displacing socioecological crises to new spatial and temporal scales.
Geography
Keywords: Canada; Ontario; Polanyian-O'Connor approach; air pollution; fictitious commodities; human ecology; infrastructure; infrastructure and the environment; neoliberal environmental fix; privatization; saving and investment; second contradiction of capitalism; social movements; socioecological fix; spatial fix

Sharing Economy: A Step towards the Re-embeddedness of the Economy? - Pais, Ivana; Provasi, Giancarlo (Stato e Mercato, 2015)
The expression "sharing economy" has spread exponentially in the past few years, a sign of the growing interest in a phenomenon that continues to maintain boundaries that are somewhat vague. The hypothesis of this paper is that this can be attributed not only to the pervasiveness and enabling power of new technologies but also to the need to fill a social vacuum due to the failures of the market and the state. The sharing economy is introducing collaborative social forms able (at least ideally) to embed economic relations within social ones. To test this hypothesis, the article uses the instrumentation implemented by Karl Polanyi to analyze the forms of integration of economy and society (exchange, reciprocity, redistribution). The political economy of the late twentieth century was especially interested in exchange (market) and redistribution (state), leaving social reciprocity in the background. However, we have to look at this more carefully to grasp any social and institutional innovation that the sharing economy can promote. The first part of this paper is devoted to an analysis of the forms of integration and, in particular, to reciprocity in its different variants. The second part, in light of the taxonomy proposed in the first, analyzes some of the most significant experiences of the sharing economy, seeking to determine the institutional characteristics and social dynamics that this could (at least potentially) engender and support. The conclusions will attempt to answer the questions formulated and indicate avenues for further research.
Economics; Sociology
Keywords: cooperative enterprises; economic anthropology; economic sociology; market structure; pricing; and design; open source products and markets; other economic systems: general; prices; public goods; reciprocity; renewable resources and conservation: demand and supply; sharing economy; social and economic stratification

Herculean efforts are not enough: diversifying the teaching profession and the need for systemic change - Schmidt, Clea (Intercultural Education, 2015)
Internationally educated teachers (IETs) seeking to resume their careers in Canada often demonstrate tremendous endurance, fortitude, and resilience in the process of navigating their new professional landscapes, yet neoliberalism and the myth of meritocracy obscure the pervasive systemic barriers characterizing their professional experiences. Critical action research undertaken with graduates of an academic and professional bridging program for IETs in Manitoba reveals a complex interplay of challenges with respect to diversifying the teaching force in intercultural settings. Data collected with IETs seeking full-time teaching positions suggest resuming their careers is by no means guaranteed for many IETs who, in spite of what can be deemed herculean efforts to follow the advice of mentors and make themselves as ‘marketable’ as possible, continue to face significant barriers to employment in a context largely characterized by an over-supply of qualified applicants. Guided by Cummins’ work on collaborative relations of power and a Polanyian critique of economic determinism, my analysis illuminates a multi-pronged systemic approach that has the potential to help ensure the numerous contributions of IETs in Canadian schools can be fully realized.
Education
Keywords: Canada; career development; collaborative relations of power; critical theory; economic determinism; equity; internationally educated teachers; professional education; systemic barriers; teacher development; teachers

Re-Imagining Economic Sociology - Aspers, Patrik; Dodd, Nigel (Oxford University Press, 2015)
The purpose of this book is to explore new developments in the field of economic sociology. It contains cutting-edge theoretical discussions by some of the world's leading economic sociologists, with chapters on topics such as the economic convention, relational sociology, economic identity, economy and law, economic networks and institutions. The book is distinctive in a number of ways. First, it focuses on theoretical contributions, by pulling together and extending what the contributors believe to be the most important theoretical innovations within their own particular areas of the field. Second, there are contributions by leading economic sociologists from both the US and Europe, which gives the book both wider scope and appeal, while also creating the opportunity for some interesting dialogue between distinct theoretical traditions. The book will be of interest to researchers, Ph.D. students, and advanced students on both side of the Atlantic, and indispensible in advanced economic sociology courses.
Sociology
Keywords: business & economics; economic sociology; economic theory; social science / sociology / general

Emancipation, marketisation, and social protection: the female subject within vocational training policy in Canada, 1960–1990 - Pullman, Ashley (Gender and Education, 2015)
This paper examines Canadian federal and cross-provincial higher education policy from 1960 to 1990, a critical time when provisions for vocational and adult training came under the auspices of governmental concern, justified under both an economic rationale and as a way to address persistent forms of inequality. The problematisation of skill during this period had particular gendered implications, as addressing inequality through education subsidies intersected with the perceived training needs of employers and the market. Employing Nancy Fraser's theory of a ‘triple movement’, the following paper ‘takes stock’ of how the three political forces of social movements, marketisation, and social protection have shaped gendered discourses of education and training, the implications for which are of continued relevance to those trying to understand the education and training within the contemporary neo-liberal state.
Education
Keywords: Canada; education policy; gender; historical sociology; history; institutional analysis; social protection; vocational education and training; welfare; workfare

Disembedded markets as a mirror of society - Deutschmann, Christoph (European Journal of Social Theory, 2015)
In the Marxist tradition, capitalism is understood as a commodified society based on markets. The article argues that the ultimate justification of this position does not lie in any ‘materialistic’ approach, but in the disembedding of markets that was the result of the historical ‘Great Transformation’ analysed by Karl Polanyi. Disembedded markets are not an economic subsystem within society but take the place of the most encompassing social system, which Durkheim had reserved for religion. The article distinguishes between spatial, social, material and temporal dimensions of disembedding, thereby elaborating and correcting the analysis of Karl Polanyi. As a genuine form of society, disembedded markets give rise to the epistemological dilemma, which, as Luhmann had shown, is fundamental to any encompassing social theory: Society as a whole cannot be viewed by any observer. According to this viewpoint, economic theories take on ‘theological’ functions, as they provide rationality and legitimacy to a reality that is unknowable.
Sociology
Keywords: Marxist philosophy; capitalism; disembedded markets; disembedding; markets; religion; social theory; uncertainty

Polanyi in the European Single Market: The Re- Regulation of Insurance - Mabbett, Deborah (Economic Sociology: The European Electronic Newsletter, 2015)
This article discusses the difference between a social policy approach to the regulatory embedding of a market and a moral economy approach using the insurance case wherein the European Union's Court of Justice ruled that insurers may not discriminate on grounds of sex in identifying risks.
Political Science; Sociology
Keywords: Court of Justice of the European Union; insurance; lawsuits & claims; reembedding; regulation; social policy

A hidden counter-movement? Precarity, politics, and social protection before and beyond the neoliberal era - Harris, Kevan; Scully, Ben (Theory & Society, 2015)
To grasp what might exist beyond neoliberalism, we need to rethink the history of development before neoliberalism. This article makes two arguments. First, for poorer countries, processes of commodification which are highlighted as evidence of neoliberalism often predate the neoliberal era. Third World development policies tended to make social and economic life more precarious as a corollary to capital accumulation before neoliberalism as an ideology took hold. Second, the intense theoretical and discursive focus on neoliberalism has obscured a tangible shift towards de-commodification in much of the global South. The most salient examples today are state-led social assistance programs that have been implemented across the former Third World. These emerged not out of technocratic fixes from above but often out of political and social struggles from below. The rise and spread of these programs are not only in stark contrast to popular conceptions of a neoliberal reinforcement, but are also specifically targeted at social strata whose precarity commonly originated in developmental policies before the neoliberal era. Utilizing a database of 183 active flagship social assistance programs in 84 developing countries, we present macro-level quantitative evidence of the rise and spread of social protection policies over the past two decades in the global South. We then detail these programs for four middle-income countries-China, Brazil, India, and South Africa. To those who lament that the 2008 crisis has produced no Polanyian double movement, we argue that these state-driven social assistance policies are such a mechanism.
Sociology
Keywords: Global South; abstracts; countermovement; developing countries; double movement; global south; ideology; labor studies; labour studies; middle-income countries; neoliberalism; peasant studies; social policy; social services; welfare studies

Markets and Society - Zaman, Asad (Social Science Research Network, 2015)
In face of the strong conflict between market norms and social norms, peaceful co-existence is impossible. In traditional societies, markets were subordinated to society. Modern society emerged via a number of revolutions which made society subordinate to markets. This led to a reversal of traditional values of social cooperation and harmony with nature. Instead, men, nature, society became objects to be exploited for creating profits. A market society generates profits by exploiting men and nature, and requires increasing profits to sustain itself. This process has run into its limits as planetary resources are being destroyed on a scale large enough to threaten the planet. Saving the planet requires reversing the transition to modernity by subordinating markets to society. This is a difficult task.
Economics
Keywords: Great Transformation; The (Book); environmental economics; exploitation; market society

Regulatory Transformations: Rethinking Economy-Society Interactions - Lange, Bettina; Haines, Fiona; Thomas, Dania (Bloomsbury Publishing, 2015)
The issue of whether transnational risk can be regulated through a social sphere goes to the heart of what John Ruggie has described as 'embedded liberalism': how capitalist countries have reconciled markets with the social community that markets require to survive and thrive. This collection, located in the wider debates about global capitalism and its regulation, tackles the challenge of finding a way forward for regulation. It rejects the old divisions of state and market, citizens and consumers, social movements and transnational corporations, as well as 'economic' and 'social' regulation. Instead this rich, multidisciplinary collection engages with a critical theme-the idea of harnessing the regulatory capacity of a social sphere by recognising the embeddedness of economic transactions within a social and political landscape. This collection therefore explores how social norms, practices, actors and institutions frame economic transactions, and thereby regulate risks generated by and for business, state and citizens.A key strength of this book is its integration of three distinct areas of scholarship: Karl Polanyi's economic sociology, regulation studies and socio-legal studies of transnational hazards. The collection is distinct in that it links the study of specific transnational risk regulatory regimes back to a social–theoretical discussion about economy–society interactions, informed by Polanyi's work. Each of the chapters addresses the way in which economics, as well as economic and social regulation, can never be understood separately from the social, particularly in the transnational context.Endorsement'This thought-provoking collection asks the most critical question of our time – how to civilise markets through social accountability and political action. The climate and financial crises we face show how crucial this challenge is. Lange, Haines and Thomas have put together a series of fruitful case studies of the possibilities for embedding economic relationships in social relationships by a series of top-class researchers within their own illuminating and sensitive framing of the issue'.Professor Christine Parker, Professor of Regulatory Studies at Monash University.
Law; Sociology
Keywords: administrative law & regulatory practice; economic regulation; economic sociology; embedded liberalism; social regulation; socio-legal studies

The Next Safety Net - Colin, Nicolas; Palier, Bruno (2015)
As the economy becomes more automated and digitized, patterns of employment will change dramatically, and social policy will need to evolve too. Instead of relying guaranteed jobs or income, write experts Nicolas Colin and Bruno Palier, governments should embrace the “flexicurity” at the heart of the Nordic model.
N/A
Keywords: automation; economy; employment; flexicurity; robots; safety net; social policy

Markets, Nature, and Society Embedding Economic & Environmental Sociology - Kaup, Brent Z. (Sociological Theory, 2015)
Social scientists have drawn on theories of embeddedness to explain the different ways legal, political, and cultural frameworks shape markets. Often overlooked, however, is how the materiality of nature also structures markets. In this article, I suggest that neo-Polanyian scholars, and economic sociologists more generally, should better engage in a historical sociology of concept formation to problematize the human exemptionalist paradigm their work upholds and recognize the role of nature in shaping markets and society. Unearthing nature in the work of Karl Polanyi, I develop a theory of embeddedness that more closely accounts for the economic, the social, and the ecological. In doing so, I provide a way for scholars to conceptualize both how market societies shape nature and how nature shapes market societies.
Sociology
Keywords: ecology; embeddedness; environmental sociology; materiality; socionatural

The meta-crisis of secular capitalism - Milbank, John; Pabst, Adrian (International Review of Economics, 2015)
The current global economic crisis concerns the way in which contemporary capitalism has turned to financialisation as a double cure for both a falling rate of profit and a deficiency of demand. Although this turning is by no means unprecedented, policies of financialisation have depressed demand (in part as a result of the long-term stagnation of average wages) while at the same time not proving adequate to restore profits and growth. This paper argues that the current crisis is less the ‘normal’ one that has to do with a constitutive need to balance growth of abstract wealth with demand for concrete commodities. Rather, it marks a meta-crisis of capitalism that is to do with the difficulties of sustaining abstract growth as such. This meta-crisis is the tendency at once to abstract from the real economy of productive activities and to reduce everything to its bare materiality. By contrast with a market economy that binds material value to symbolic meaning, a capitalist economy tends to separate matter from symbol and reduce materiality to calculable numbers representing ‘wealth’. Such a conception of wealth rests on the aggregation of abstract numbers that cuts out all the relational goods and the ‘commons’ on which shared prosperity depends.
Economics
Keywords: abstraction; financialisation; financialization; materialisation; meta-crisis

Karl Polanyi and the Problem of Corporate Social Responsibility - Moncrieff, Lilian (Journal of Law and Society, 2015)
This article considers Corporate Social Responsibility (CSR) as part of the projects in ‘new governance and decentred regulation’, which draw social forces towards the regulation of economic behaviour. It uses Karl Polanyi to open up pertinent interfaces between society and economy for observation, and Gunther Teubner to substantiate a ‘regulatory’ view of the company's social relationships. The article finds that CSR combines movements for the recognition of social relationships, on an unprecedented scale, with rigorous simultaneous movements for market building and social abstraction. Twenty-first-century market economy is defined by a capacity to contain ‘the social,’ which is thrown between the two movements, creating opportunities for companies to void the market's social limits. The article counterposes that the social that ‘returns’ after marketization needs to find its way past market-building CSR, to constructively unshackle and redefine the framing of social conflicts that concern the corporation.
Law; Sociology
Keywords: CSR; corporate social responsibility; marketization

Benjamin Cohen on global political order: when Keynes meets realism – and beyond - Guzzini, Stefano (Contexto Internacional, 2015)
This article analyses the trajectory of Benjamin J. Cohen's work by focusing on his ongoing concern with the nature and governance of world order. It does so by playing out his debt to realism and to Keynesianism. In a first moment, Cohen criticises the economic determinism of dependency scholarship, while turning to political realism, and then to possible Keynesian co-operation under anarchy: agents have the power to affect positive change. Later, Cohen the disillusioned Keynesian, watching how the possible reform of financial markets is marginalised by politicians and academics alike, shifts his analysis to more structural aspects of governance or rule that affect actors' preferences. I draw two conclusions. First, in this shift towards theorising the global political order away from steering capacity towards impersonal rule and bias, Cohen also questions the very setup of the theories with which we deal with that world – only to see that this very inspiration of original IPE is abandoned in the course of the ongoing ‘professionalisation' of IPE as practised in the United States. Second, his analysis seems to incorporate a warning. The underlying grand question is nothing less than the bargain between capitalism and liberal democracy as we know it, since the present system undermines equality before the law – money trumps equal political rights – and undermines democratic accountability. One of the main achievements of the post-war Keynesian turn was the reappropriation of political space from anti-democratic forces. Therefore, the decline of Keynesianism could provoke a Polanyian nightmare in which the ‘double movement' by which the laissez-faire is answered by moves to protect society does not strengthen democracies, as in earlier times of ‘embedded liberalism', but undermines them instead.
Political Science; International Relations
Keywords: COHEN; Benjamin J.; Keynesian economics; capitalism; dependency; embedded liberalism; global governance; international finance; international relations; political realism; securities markets; structural power

The political economy of orphanage tourism in Cambodia - Guiney, Tess; Mostafanezhad, Mary (Tourist Studies, 2015)
A recent Aljazeera report on ‘Cambodia’s Orphan Business’ explains ‘how “voluntourism” could be fuelling the exploitation of Cambodian children’. Anti-orphanage tourism movements have emerged to resist the growth of Cambodia’s contested orphanage tourism industry, which is blamed for widespread corruption and the exploitation of children for profit. Taking a Polanyian political economy approach, this article illustrates how the emergence of and response to the orphanage tourism industry represent, in Karl Polanyi’s words, a ‘double movement’ between the neoliberalization of orphanages and the corollary protective countermovement by anti-orphanage tourism campaigns that challenge the industry’s morality and legitimacy. It argues that while resistance to the commodification of orphanages under the newly neoliberalized Cambodian economy reflects Polanyi’s double movement thesis, the limits of this resistance are also indicative of how countermovements are challenged by the broader political economy in which they operate.
Geography
Keywords: Cambodia; double movement; hospitality; leisure; sport & tourism; orphanage tourism; tourism; tourist studies; volunteer tourism

Land as fictitious commodity: the continuing evolution of women's land rights in Uganda - Naybor, Deborah (Gender, Place & Culture: A Journal of Feminist Geography, 2015)
In sub-Saharan Africa, colonial influences have altered traditional practices as a way to manage that which Polanyi labeled as ‘fictitious commodities’ of land, labor, and money. Land has now become a highly marketable commodity and an intrinsic part of the global economy. Over the past century, Uganda's land rights have evolved from communal rights to that of male-dominated, individual ownership practices that have excluded women. Despite constitutional provisions, which confer title of both a deceased husband's property rights and equal rights to property within a marriage to a wife, postcolonial patriarchal tradition prevails. This article examines historical changes in land rights in Uganda and discusses the impact of shifts in land rights from communal ownership to individual tenure, altering power structures and attempting to create marketable land title. The Ugandan women's movement's opposition to policies and implementation of laws that exclude women has been unable to facilitate the required changes in unbiased access to land rights, despite apparent victories in revisions to the letter of the law. Situated within contemporary interpretations of tradition and pressures of market demand, this article shows that women's access to landownership and use are restricted by misinterpretation of traditional law and a lack of enforcement of contemporary legal rights. To illustrate the impact of a lack of access to land, this article examines an empirical case study of widowed subsistence farmers in southern Uganda. Women in Uganda continue to lose ground, quite literally, decreasing the possibility of gender equity in terms of land. (English)
Geography
Keywords: Uganda; derechos de las mujeres; free enterprise; gender; género; land; land tenure; legal status of widows; legal status of women; property rights; tierra; viuda; widow; women's rights; 乌干达; 土地; 女性权利; 寡妇; 性别

Europe at a Crossroads: Failed Ideas, Fictional Facts, and Fatal Consequences - Thomasberger, Claus (Forum for Social Economics, 2015)
The crisis of the European Monetary Union has revealed the weakness and the fragility of the European integration process. The paper examines the institutional changes which are at the root of the instability. What are the driving forces behind the introduction of the euro? What role do theoretical considerations play in this process? What influence on European integration has been exerted by neoliberal beliefs and convictions? Relying on an approach that combines basic insights of Gunnar Myrdal with Karl Polanyi's idea of a "double movement," it concentrates on the institutional transformation that is at the basis of the European integration process. The relationship between (misleading) ideas and facts is at the center of the study. It examines the influence of ideas and theoretical models on European integration, the Single Market Program, the Maastricht process, the increasing imbalances since the introduction of the euro, and the strategies applied during the recent crisis.
Economics; Philosophy
Keywords: economic integration; financial aspects of economic integration; financial crises; international institutional arrangements

Hard cash, easy credit, fictitious capital: Critical reflections on money as a fetishised social relation - Jessop, Bob (Finance and Society, 2015)
Sociology
Keywords: Marxism; commodity; credit; debt; fictitious capital; money

Marketization: Theoretical Reflections Building on the Perspectives of Polanyi and Habermas - Ebner, Alexander (Review of Political Economy, 2015)
The concept of marketization denotes the expansion of market coordination into non-market coordinated social domains as well as its intensification in already market-dominated settings. This article sets out to reconstruct an institutionalist theory of marketization. As a point of departure, it critically examines the related contributions of Karl Polanyi and Jürgen Habermas. The analytical strength of Polanyi's theory of marketization lies in the discussion of the contested embeddedness of markets and the view of marketization as a politically shaped process of institutional change. This concern with the societal expansion of markets is further developed in the Habermasian thesis of the ‘colonisation of the lifeworld’. However, both Polanyi and Habermas lack a specification of the social substance of markets and thus tend to underestimate the complexity of marketization. To address this issue, the present article utilizes the concept of collective goods to introduce new arguments about the institutional dynamics of marketization in the diverse fields of society.
Sociology; Political Science
Keywords: HABERMAS; Jurgen; collective goods; economics; embeddedness; marketization; markets; socioeconomics

Goody, Polanyi and Eurasia: An Unfinished Project in Comparative Historical Economic Anthropology - Hann, Chris (History & Anthropology, 2015)
Goody's essay overlaps with his recent work on the “search for metals” and, more generally, with his many books expounding the commonalities of Eurasian history. His critique of Eurocentrism remains invaluable. This review article argues that his emphasis on diffusion can be usefully supplemented with a concept of civilization, to facilitate comparative structural analysis. Goody's perspective might also be enhanced by an engagement with the literature on “Axial Age” cosmologies and with substantivist economic anthropology. It is worth revisiting Karl Polanyi's efforts to grasp the position of the economy in society, in order to recover in the neoliberal present the long-run Eurasian dialectic between redistribution and market exchange.
Anthropology
Keywords: Eurasia; GOODY; Jack; 1919-2015; civilization; culture diffusion; economic anthropology

Polanyi, Hayek, and the Impossibility of Libertarian Ideal Theory - Lindsay, Peter (Polity, 2015)
In 1944, two seminal works of political and social theory appeared: F.A. Hayek's The Road to Serfdom and Karl Polanyi's The Great Transformation. Both works focused on society's spontaneous resistance to the 'marketization' of life. Yet, the authors arrived at opposite normative conclusions. This article attributes the normative distance to a methodological clash over the role and limits of normative theorizing in the concrete and sometimes uncooperative world of politics. This clash, in turn, illuminates recent debates about 'ideal' and 'non-ideal' theory, and suggests limits to the applicability of the former.
Political Science
Keywords: Great Transformation; The (Book); HAYEK; Friedrich A. von (Friedrich August); 1899-1992; Road to Serfdom (book); free enterprise; free markets; ideal theory; laissez-faire; libertarian theory; non-ideal theory

Marketization and the public-private divide - Rekhviashvili, Lela (International Journal of Sociology & Social Policy, 2015)
Purpose – The purpose of this paper is to critically examine the reasons behind a decade long contestations between the Georgian government and the petty traders over the access to the public space for commercial use. Design/methodology/approach – The paper relies on the repeated ethnographic fieldwork conducted in Tbilisi in 2012 and 2013. The ethnographic interviews with legally operating traders and illegal street vendors are supplemented by the in-depth interviews with the representatives of the city government and secondary literature on Georgia’s post-revolutionary transformation. Findings – Bridging the critical literature on the politics of the public space with Polanyi’s theory on commodification of fictitious commodities as a precondition of establishment of a market economy, the author argues that for the Georgian government control of the public space was necessary to pursue neoliberal marketisation policies. These policies required removal of the petty traders from public spaces because the state needed to restrict access to public space and limit its commercial usage to delineate public and private property and allow commodification of the urban land and property. As the commodification intensified and the rent prices started growing and fluctuating, the access to the public space became even more valuable for the petty traders. Therefore, the traders developed subversive tactics undermining the division between public and private space and property. Originality/value – The paper demonstrates the importance of enforcing the public-private divide in the process of establishing a market economy in transitional settings. Moreover, it illustrates little discussed social costs of establishing such a divide.
Sociology
Keywords: Tbilisi; commodification; fictitious commodities; informal economy; marketization; municipal government; neoliberalism; petty trade; public space; public spaces; public-private sector cooperation; transition economies

The Neoclassical Origins of Polanyi’s Self-Regulating Market - Gemici, Kurtuluş (Sociological Theory, 2015)
This article shows, through a detailed examination of Karl Polanyi’s published works and unpublished writings, that Polanyi relies heavily on the neoclassical economics of his time in his conceptualization of the market in capitalist societies. This approach is instrumental to the thesis of The Great Transformation concerning the destructive impact of the market on society. However, such an analytical perspective neglects the social character of the market economy. This perspective is also deficient in capturing why the market is destructive to the social fabric. By identifying the origins and limitations of Polanyi’s self-regulating market, this article contributes to critical reevaluations of his work that aim to expand the scope of Polanyian analysis. In particular, this article outlines how the analysis of the market’s contradictory place is not predicated on the notion of self-regulation. Polanyi’s own historical work, as opposed to his theoretical articulations, illustrates such an analysis.
Sociology
Keywords: double movement; neoclassical economics; self-regulating market

Migration, Precarization and the Democratic Deficit in Global Governance - Schierup, Carl-Ulrik; Ålund, Aleksandra; Likić-Brborić, Branka (International Migration, 2015)
This article attempts to provide a critical understanding of the dual signification of “precarity”. It explores what “precarity” as a concept may potentially offer to studies of the changing contemporary political economy of migration. It discusses shifting trends in global migration and point to tendencies for a possible convergence between “South” and “North”, “East” and “West”. Based on a review of current advances in research, it discusses, with reference to the classical work of Karl Polanyi, the potential for a contemporary “countermovement” which would challenge the precarity of migrants. Bringing forward the issue of the “space for civil society” the article addresses a still lingering democratic deficit in the global governance of migration. Policy Implications The article is relevant to policymakers, trade unions and civil society organizations. It contributes to the understanding of policy making processes in emerging multilevel global governance and focuses on issues of precarization, migration, and the implementation and accountability of human, migrant and labour rights.
Sociology; Anthropology
Keywords: countermovement; democratic deficit; ethnicity; global governance; migration; precarity; social welfare studies

Book Review Essay: The Environmental Crisis and Its Capitalist Roots: Reading Naomi Klein with Karl Polanyi*—Naomi Klein: This Changes Everything: Capitalism vs. the Climate - Adler, Paul S. (Administrative Science Quarterly, 2015)
An essay is presented on the relationship between climate change and capitalism, offering a reading of the argument in "This Changes Everything: Capitalism vs. the Climate" by Naomi Klein through the lens of the analysis in "The Great Transformation" by Karl Polanyi. The author suggests that Klein's argument is not clear on whether capitalism in any form or only the current, neoliberal version of capitalism is incompatible with effective action to address the problem of climate change. Topics include environmental externalities and policies addressing them, the environmental record of corporations, and the theory of the self-regulating market.
Business; Management Studies; Administrative Science
Keywords: Great Transformation; The (Book); KLEIN; Naomi; This Changes Everything (Book); business enterprises & the environment; capitalism; climatic changes; economic aspects; environmental policy; externalities

Between Marx and Polanyi: New labour mobilisations in the Italian crisis - Caruso, Loris (Capital & Class, 2015)
The current scenario in western countries is characterised by a crisis over the last thirty years of class conflict; by the mainly negative consequences of globalisation and of the transformations by production processes of the mobilising strength of work; by the cancellation of the relationship between labour and political representation; by the difficulties of traditional trade unionism; and by the emergence of the social movement unionism (SMU) paradigm. In this article, these phenomena are analysed from the point of view of the workers’ struggles against the closure of factories. The analysis concerns the mobilisation factors on which the struggle rests; the presence or absence, in the representations of workers, of references to class conflict; the major proximity of these mobilisations to the paradigm of traditional syndicalism or to the SMU paradigm; and the prevalence within them of the Marxist or the Polanyian root of conflict. This analysis is mainly based on an empirical study carried out in an engineering company in the province of Milan, Italy.
Sociology
Keywords: MARX; Karl; 1818-1883; class cleavage; class conflict; crisis; globalisation; globalizaton - research; labor mobility; labor unions; labour mobilisations; labour mobility; labour unions; research; social conflict; social movements

Hayek versus Polanyi: Espontaneidade e designio no capitalismo. (Hayek versus Polanyi: Spontaneity and Design in Capitalism. With English summary.) - de Almeida, Rafael Galvao; Garcia Fernandez, Ramon (Economica (Fluminense Federal University), 2015)
This work introduces the concept of spontaneous order, its development through many schools of economic thought and its importance to today's society. This paper gives emphasis to Friedrich Hayek, since he has the most known model of spontaneous order, how he started to elaborate from his research about the role of the information on the economy and his maturation in Law, Legislation and Liberty. As a counterpoint to the Hayekian model, this work includes criticism to the concept and the work of Karl Polanyi is analyzed. He diverged from Hayek about the role of the market in the society, when he affirmed that society protects itself from the invasion of the market in the other social spheres, through the process of double movement. Lastly, it is concluded that there is no evidence to discard the existence of spontaneous orders; the double, that double movement, because it is started with the individuals before taking legislative form, has the necessary characteristics to be considered a type of spontaneous order; and, due to the self-organizational trait of spontaneous order, there are practical problems in political anarchism.
Economics
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; belief; communication; elections; history of economic thought; information and knowledge; learning; legislatures; lobbying; market structure; pricing; and design; political processes: rent-seeking; lobbying; elections; legislatures; and voting behavior; rent-seeking; spontaneous order; unawareness; voting behavior

Strengthening Karl Polanyi’s Concepts of Reciprocity, Double Movement, and Freedom with the Assistance of Abductive Logic - Hayden, F. Gregory (Journal of Economic Issues (Taylor & Francis Ltd), 2015)
My purpose here is to strengthen Karl Polanyi’s work through critique of and extension to abductive processes. Polanyi presented history woven into a new paradigm for analysis of socioeconomic systems, demonstrated discovery similar to abductive processes, and extended abduction into a holistic context. One of Polanyi’s most important contributions to socioeconomic analysis is the explanation of three integrated network models of socioeconomic reciprocity. They are coadjuvancy, redistribution, and market exchange. Polanyi extended abductive reasoning in two ways. First, he extended it beyond the cognitive logic of a person to inferences and societal belief changes of institutions. Second, he showed that, in the real world, beliefs are not only fixed like an abductive process, they are fixed in law. Throughout Polanyi’s historical presentation, market beliefs are being revised, thus serving as a demonstration of the abductive process. I make both positive and negative critique of a number of Polanyi’s concepts, with special attention to reciprocity, the double movement, and freedom. This critique and abduction extension strengthens Polanyi’s paradigm for future socioeconomic analysis with his integrative network models.
Economics
Keywords: abductive logic; beliefs; double movement; economic theory; freedom; production; reciprocity; reciprocity (commerce); socioeconomic; socioeconomics; stock exchanges

Gellner’s genealogy of the open society: Biopolitics as fragment and remainder - Ryan, Kevin (Thesis Eleven, 2015)
A decade before Foucault began to work with the related concepts of biopolitics and biopower, Gellner posed a series of questions which are suggestive of a similar line of inquiry. Gellner did not pursue this strand of his thought as an historical sociologist however. Instead he packaged it into a functionalist account of how industrial society reproduces itself. In Gellner’s writings, biopolitics is both present and absent, like a redacted text. This is the focus of this article, which locates Gellner’s method of inquiry within a corpus of genealogical studies that includes the work of Polanyi, Weber and Foucault. What distinguishes Gellner is that the history he reconstructs is a story of achievement in the face of terrible historical odds, but this culminates in a normative genealogy that limits the scope for critical analysis. The article concludes by adopting an alternative – yet still Gellnerian – approach to the question of social reproduction, thereby using Gellner to critique Gellner.
Political Science; Sociology
Keywords: FOUCAULT; Michel; 1926-1984; GELLNER; Ernest; biopolitics; biopolitics (philosophy); biopower; genealogy; historical sociology; realism; social aspects

Basic Income, Full Employment, and Social Provisioning: Some Polanyian/Keynesian Insights - Seccareccia, Mario (Journal of Economic Issues (Taylor & Francis Ltd), 2015)
The purpose of this article is to offer a Polanyian perspective on the issue of guaranteed income (GI). In analyzing the debate over the Speenhamland system, especially as Karl Polanyi ([1944] 2001) describes it inThe Great Transformation, he offered an important criticism of a GI program that some contemporary Polanyian economists have been struggling to come to terms with in their writings. Instead of defending a GI policy by seeking to reject Polanyi’s analysis of the problem, I suggest that we should consider embracing Polanyi’s concern by proposing a comprehensive twin policy that would complement a basic income program with a Keynesian full employment commitment.
Economics
Keywords: English Poor Laws; Keynesianism; Speenhamland system; basic income; economists; full employment; full-time employment; guaranteed annual income; income; income supplementation

Provision of Social Costs and the Free Market: A Polanyian Perspective - Vidal, Gregorio; Marshall, Wesley; Correa, Eugenia (Journal of Economic Issues (Taylor & Francis Ltd), 2015)
In this article, we analyze at a conceptual level some of the more relevant effects of the neoliberal takeover on the provision of social costs, including employment, health care, and nutrition. Adopting key perspectives of Karl Polanyi and other thinkers, we develop our examination under the seemingly perpetual conflict between markets and social reproduction. We argue that financialization has both expanded market spaces and changed relationships within those spaces. The ever-greater domination of financial markets means that employment has become increasingly more precarious in the strict spaces of the labor market. At the same time, financialization has steadily eroded the social forms that exist outside of formal markets, greatly weakening the mechanisms through which societies can both defend themselves from predatory markets and reproduce themselves with some degree of purpose and hope for the future.
Economics
Keywords: employment (economic theory); externalities; externalities (economics); financialization; free enterprise; neoliberalism; nutrition; social reproduction

Corporate Power and Responsible Capitalism?: Towards Social Accountability - Jones, Bryn (Edward Elgar Publishing, 2015)
In this important book, Bryn Jones uses insights from political economy, historical analysis and sociological concepts of the corporation, as a socially disembedded but political actor, to address concerns over the over-reach of Anglo-Saxon corporation KM – on page 6: "Following Karl Polanyi, I argue that ST/EM firms have outgrown and threaten to dominate, envelop and even undermine, some of the social and political institutions on which a sustainable market economy depends. Any rebalancing of the relationship between corporations and the rest of society must therefore interrogate the nature of the relationship between market organisations, such as firms, and the social institutions to which they are linked.
Economics; Business Studies
Keywords: ST/EM corporations; business & economics; business ethics; business systems; corporate governance; disembedding; executive managed corporations; industrial management; management; management science; organizational behavior; share-traded corporations; social embedding

The course, contradictions, and consequences of extending competition as a mode of (meta-)governance: towards a sociology of competition and its limits - Jessop, Bob (Distinktion: Journal of Social Theory, 2015)
This article examines the use of competition as an object and mode of governance. It first considers how competition might become a principle of economic organization and, relatedly, how it may become part of state projects and practices. Second, it comments on the discursive and material dimensions of competition, considering it as a social construct and as a social constraint. Third, it examines the rather idealized representations of competition in the broader doxa of liberalism and neo-liberalism considered in terms of a rough threefold distinction among economic, political, and ideological imaginaries and the limits to the reproduction of these doxa in terms of the complexities of capitalist social relations. Fourth, it explores the complexities of competition in the actually existing world and their role in differential accumulation. In this context it distinguishes neo-classical, Austrian, and Schumpeterian views on competition and entrepreneurship and their contribution to equilibration or creative destruction. Fifth, it considers efforts to steer competition through, inter alia, the competition state and competition law. Sixth, it relates competition to other modes of governance and identifies limits to its role in this regard and introduces ‘meta-governance’ as a response to these limits. Finally, seventh, it comments on the fetishization of competition as a means to subsume society under the dominance of profit-oriented, market-mediated accumulation. It concludes with comments on the limits of competition in relation to fictitious commodities and goods and services that contribute to human flourishing.
Sociology
Keywords: commodification; competition; competition law; competition state; competitiveness; governance; neoliberalism; new public management; social theory

The Bioeconomy as Political Project: A Polanyian Analysis - Goven, Joanna; Pavone, Vincenzo (Science, Technology & Human Values, 2015)
The bioeconomy is becoming increasingly prominent in policy and scholarly literature, but critical examination of the concept is lacking. We argue that the bioeconomy should be understood as a political project, not simply or primarily as a technoscientific or economic one. We use a conceptual framework derived from the work of Karl Polanyi to elucidate the politically performative nature of the bioeconomy through an analysis of an influential Organization for Economic Cooperation and Development (OECD) initiative, The Bioeconomy to 2030. We argue that this initiative is a response to some of the most acute challenges facing the current neoliberal-capitalist accumulation regime, which seeks to protect and extend that regime, through both what it occludes and what it promotes. Rather than taking the bioeconomy as a description of some subset of economic activity, we regard it as a promissory construct that is meant to induce and facilitate some actions while deterring others; most explicitly, it is meant to bring about a particular set of political–institutional changes that will shape the parameters of possible future action. The bioeconomy concept highlights the potential dangers of failing to situate ethnographic examinations of horizontal micro-relations within a political–economic macro-context that enables and constrains. Scholarly work in science and technology studies and elsewhere that does not recognize the wider politics of the bioeconomy risks unintentionally contributing to the legitimation of this political project.
Political Science
Keywords: bioeconomy; commodification; cooperation; economics; ethnographic analysis; futures; inequality; literature; markets/economies; neoliberalism; organization; politics

Authoritarian Liberalism in the European Constitutional Imagination: Second Time as Farce? - Wilkinson, Michael A. (European Law Journal, 2015)
The current crisis in Europe recalls the theory and practice of authoritarian liberalism, the idea that in order to protect economic liberalism and respect for fiscal discipline, representative democracy must be curtailed. This configuration was first identified by Hermann Heller in late Weimar as a response to the imperative to maintain the ideological separation of state and economy and presented by Karl Polanyi as conditioned by broader geo-political pressure to maintain the gold standard in the inter-war period. Authoritarian liberalism is now conditioned by conflicting imperatives to maintain the project of the single currency, respect ordo-liberal concerns of moral hazard, and protect 'militant democracy' but only in one country. Does this reflect a broader geo-political disequilibrium, due to tensions between market integration, constitutionalism and democracy?
Law
Keywords: Europe; European Sovereign Debt Crisis; 2009-; HELLER; Hermann; 1891-1933; POLANYI; Karl; 1886-1964; authoritarianism; constitutionalism; democracy; equilibrium (economics); liberalism

The Great Mindshift: Linking Forerunners of a New Sustainability Paradigm - Gopel, Maja (Brookings Inst Press, 2015)
Making sustainability a policy goal is one of the greatest challenges of the 21st century. Calls for a paradigm shift are becoming increasingly frequent and urgent. In fact, change toward a sustainable form of society seems to be more within reach than ever before. The mindset of people has changed in the course of economic and environmental crises. This publication presents the current scientific and practical approaches that shape and empower the process of change toward true sustainability. It also raises the question as to the new possibilities that may arise from linking these approaches.
Political Science
Keywords: environmental policy; environmental science; global warming & climate change; public policy; science

After ideocracy and civil society Gellner, Polanyi and the new peripheralization of Central Europe - Hann, Chris (Thesis Eleven, 2015)
Behind only that of Bronislaw Malinowski, the influence of the Central European polymaths Ernest Gellner and Karl Polanyi on socio-cultural anthropology in the 20th century was profound. Gellner and Polanyi also influenced much wider swathes of scholarship. They belong to different generations and were raised in quite different settings in Prague and Budapest respectively. What these thinkers have in common is a philosophy of history which posits the industrial revolution in northwest Europe as a radical rupture in Weltgeschichte. Polanyi’s ‘great transformation’, with its focus on the economy, corresponds to Gellner’s metaphor of the ‘big ditch’ and focus on a new polity. The cultural homogenization of the nation-state and the disembedding of the economy from society in the era of free trade are two sides of the same coin. This paper argues that these complementary models derive to a considerable degree from the scholars’ background on the margins of industrializing Europe, in the ruins of the Habsburg Empire.
Anthropology
Keywords: Central Europe; GELLNER; Ernest; anthropology; civil society

To boldly go (Fund Strategy, 2015)
The article provides the author's view on issues concerning free market economics. He mentions Mr. Spock, a fictional character in the "Star Trek," whom critics of free market economics often cite as the epitome of rational economic man or Homo Economicus, as well as features Karl Polanyi, a Hungarian-American economist, who opposed the idea of humans as rational economic agents in his work "The Great Transformation." He also mentions human reason and cultural pessimism.
Economics
Keywords: Spock; Mr.; capitalism; economists; free enterprise

The limits to China's non-interference foreign policy: pro-state interventionism and the rescaling of economic governance - Gonzalez-Vicente, Ruben (Australian Journal of International Affairs, 2015)
China's foreign policy has been long committed to a principle of non-interference in the internal affairs of sovereign countries. While one could easily point out past and present-day inconsistencies in its implementation, this article argues that defenders and critics of the principle both rely on a limited interpretation of ‘interference’ or ‘intervention’ based on an ideology of Westphalian sovereignty. Particularly problematic is the conceptual distinction between the ‘political’ or ‘diplomatic’, on the one hand, and the ‘economic’, on the other. As Polanyi's concept of embeddedness reminds us, markets, society and politics occur simultaneously, and can only act as discrete realms in epistemological abstractions. It is thus argued that non-interference is a semi-formal institution that governs China's diplomatic engagements and affects its economic activities. While the totality of China's interactions with the world has diverse and sometimes contradictory impacts on global governance, non-interference itself has apparent consequences for the rescaling of regional economic governance. Specifically, this article contends that Chinese non-interference results in the empowerment of political elites at national levels, and thus in the (re-)emergence of the nation state as a gatekeeper and facilitator of the advancement of capitalist enterprises. As a result, through non-intervention, China's foreign policy undermines supranational regulatory approaches and fosters state-based regional architectures.
Development Studies; International Relations
Keywords: China; China - foreign relations; People's Republic of China; Westphalians - foreign countries; bilateralism; economic policy; embeddedness; foreign policy; non-interference; socioeconomic theory; supranationalism

Explaining Political Tunnel Vision: Politics and Economics in Crisis-Ridden Europe, Then and Now - Mudge, Stephanie L. (European Journal of Sociology, 2015)
The grip of austerity in European politics since 2008 presents a double puzzle: electorally weak center-left parties offering no definite alternative, and the surprisingly efficient pursuit of “fiscal consolidation”. To understand this double puzzle this article investigates the institutional bases of alternative economic thinking during the 1930s versus the post-2008 crisis years. Noting the recent prominence of a new social type, the European economist-technocrat (eet), I highlight the historically specific order to which the eet is indigenous: rarefied, international professional circuits that tend to work over, not through, party politics. This contrasts sharply with the nationally-based, party-connected economists who developed new economic orthodoxies between the 1930s and 1960s, including Keynes himself. Approaching the study of economic culture in the public sphere in a Polanyian moral markets framework, I argue that the linkages between European economics and financial technocracies help to explain Europe’s double puzzle. Theoretically, I argue that a focus on expertise and parties, and not just states, is central to our understanding of economic culture in the public sphere. (English)
Sociology
Keywords: European Union; Europäische Union; Frachkenntnisse; Sparmaβnahmen; Union européenne; austerity; austerité; compétence; economics; economists; expertise; partis politiques; political parties; politics and economics; politischen parteien; public sphere; technocracy; wirtschaft; économie

A Neo-Polanyian Theory of Economic Crises - Block, Fred (American Journal of Economics and Sociology, 2015)
This article seeks to use Karl Polanyi's book, The Great Transformation, first published in 1944, to understand the global financial crisis that began in 2008. Polanyi's basic premise was that a great crisis must result from powerful causes. He argued that the crisis of the 1930s was a consequence of three distinct processes: deep imbalances in the global trading system, a crisis within the global financial mechanism that was supposed to manage those imbalances, and a failure of adaptation in the world's leading economy, the United States. The same processes can be seen at work in the last decade.
Sociology
Keywords: global financial crisis

Pursuing a Great Transformation - Evans, Peter (Sociology of Development, 2015)
Polanyi offers a powerful vision of a “great transformation” that will reverse the subordination of society to the economy and reassert the primacy of social protection in the context of modern society. Pursuit of the great transformation is one way of conceptualizing the quest for “development” in the positive sense of ecologically sustainable human flourishing. This paper explores how the contemporary interaction of national and global political dynamics affects the trajectory of Polanyi's “double movement.” Does the shift of economic power to globally organized capital while the space for contentious politics remains primarily at the national level “checkmate” the movement for social protection? Or is there more potential for political contestation and policies supporting social protection at the national level than the “global checkmate” thesis claims? And, if so, can this potential be magnified by productive, synergistic alliances between national and global movements, resulting in a global auxiliary effect instead of a global checkmate effect? Answering these questions requires analyzing the relative autonomy of national political regimes vis-à-vis global capital as well as evaluating the ability of movements to connect effectively across levels.
Sociology
Keywords: Great Transformation; The (Book); double movement; global capital; social protection; transnational social movements

The power of market fundamentalism: Karl Polanyi's critique - Gamble, Andrew (Cambridge Review of International Affairs, 2015)
Political Science
Keywords: BLOCK; Fred; Power of Market Fundamentalism: Karl Polanyi's Critique; The (Book); SOMERS; Margaret R.; markets; nonfiction; review

Protecting Markets from Society: Non-Pecuniary Claims in American Corporate Democracy - Gershenson, Carl (Politics & Society, 2015)
The state incentivizes investors to entrust capital to public corporations by granting shareholders enforceable rights over managers. However, these rights create legal “access points” through which social movements can make nonpecuniary claims on the corporation. I use original historical research on the Securities and Exchange Commission’s administration of federal securities law to show that concern over nonpecuniary claims motivates the state to enact the role of “market protector.” In this role, the commission insulates managers of corporations from shareholders’ claims that it deems illegitimate because they are insufficiently profit-oriented. Thus the inverse of Polanyi’s observation that society protects itself from markets is also true: the state creates market boundaries so that “always embedded” markets function more like autonomous, profit-oriented markets. Accordingly, the extent to which corporate democracy represents general, social interests or narrow, profit-oriented interests is largely a function of political contestation and state policy.
Sociology
Keywords: United States; United States Securities & Exchange Commission; corporate accountability; corporate democracy; corporations - government policy; economic sociology; legal status of stockholders; markets; markets - government policy; political sociology; social responsibility of business - United States

Reading The Great Transformation - Martin, Isaac William (Contemporary Sociology, 2015)
Karl Polanyi’s book The Great Transformation is a classic... it has come to be recognized as a founding charter for economic sociology. It anticipated major accomplishments of late-twentieth-century social science (including, among others, Ben Bernanke’s studies of the Great Depression and Amartya Sen’s work on famine). Its core problems—how do societies respond to globalization? how do they address the risks of market failure?—are central to contemporary macrosociology. It is probably time to recognize the canonical status of this book and put it on the classical theory syllabus alongside Marx, Weber, and Durkheim. But The Great Transformation is also—can we admit this about our classics?—a mess. It is conceptually sloppy. Some key terms (such as “market society” and “social dislocation”) are never explicitly defined. Others (such as “a ‘movement’”) are defined with pedantic care, and then used willy-nilly, as if Polanyi forgot what he said the words meant. Important steps in the argument assume what is to be proven. Inconsistencies abound. The treatment of historical sources is casual. To round it all off, the book concludes with a breathtakingly wrong prediction: namely, that the era of market liberalism is over for good—as of 1944. To salvage a theory from all this, let alone one that we can apply to societies in the present day, surely requires a heroic effort of interpretation. Fred Block and Margaret R. Somers undertake the salvage effort...
Sociology
Keywords: BLOCK; Fred L.; Great Transformation; The (Book); Power of Market Fundamentalism: Karl Polanyi's Critique; The (Book); SOMERS; Margaret R.; book review; nonfiction

Mobilizing the depths of the market: Motivation research and the making of the disembedded consumer - Schwarzkopf, Stefan (Marketing Theory, 2015)
Twentieth-century consumer society was characterized by a process of disembedding as described by Karl Polanyi in The Great Transformation (2001 [1944]). The Austro-American consumer researcher Ernest Dichter played a key role in preparing the ideological framework necessary for this process to succeed. In order to assess Dichter’s role and that of psychoanalytic motivation research in general in the creation of the idea of the disembedded consumer, this article presents an analysis of Dichter’s unpublished consumer research reports ranging across different countries and industries between 1939 and 1973. Through content analysis and historical contextualization, I show that Ernest Dichter in particular and psychoanalytic motivation research in general were instrumental in removing from market relationships the invisible hand of social norms. The case of the consumer psychoanalyst Ernest Dichter thus provides new insights into the sociocultural mechanisms by which theorizing in consumer research can influence the objects of its theorizing.
Business; Marketing
Keywords: DICHTER; Ernest; consumer research; disembedding; interpersonal relations; market society; marketing; motivation research; pleasure principle; psychoanalysis; therapeutic ethos

Mutating Neoliberalism: The Promotion of Italian Investors in Slovakia before and after the Global Financial Crisis - Sellar, Christian; Pástor, Rudolf (International Journal of Urban & Regional Research, 2015)
In the context of the literature on 'actually existing neoliberalisms', this article analyzes the policies and services supporting Italian foreign direct investment (FDI) in Slovakia. It identifies a group of organizations, both Slovak and Italian, which shape and deliver neoliberal pro-FDI policies. By studying such an 'investment promotion community' (IPC) before and after the global financial crisis of 2009, and during Italy's prolonged crisis, this article shows both the persistence and adaptability of neoliberal policies and institutions. In so doing, it highlights some of the transnational flows underpinning the 'domestication' of neoliberalism in Slovakia. These findings support recent literature arguing that post-crisis neoliberalism can be interpreted as a stunted Polanyian double movement, in which the state has improved some of its regulatory functions but without questioning the overarching neoliberal principles. Specifically, it shows that FDI policies and the support of Italian investors rest upon a professional community that has not changed much since the 2009 crisis. This community played a crucial role in embedding neoliberal rationalities in Slovakia and supports the persistence of this ideology in the post-crisis environment.
Political Science; Public Administration
Keywords: Bratislava; Italy; Košice; Kralovsky Chlmec; Slovakia; Slovakia - economic conditions; Slovakia - foreign economic relations; capitalists & financiers; double movement; financial crisis; foreign direct investment; foreign investments; global financial crisis; 2008-2009; neoliberalism

The Evolution of the Property Relation: Understanding Paradigms, Debates, and Prospects - Davis, Anne E. (Springer, 2015)
Evolution of the Property Relation defines an approach to economics which is centered around the concept of property and explores the historical evolution of the relationship of the individual, private property, and the state, and the distinctive changes wrought by the emergence of the market.
Economics; Sociology
Keywords: business & economics; economic development; economic history; economic theory; labor; labour; management; organizational behavior; social science; sociology; strategic planning

Embedding and disembedding of political elites: a filter system approach - Davis, Aeron (Sociological Review, 2015)
This article looks at the issue of political disengagement in mature democracies and the growing tendency towards disconnect between citizens and their political representatives. It locates itself in relation to 'demand-side' (external to politics) and critical 'supply-side' (focused on the political centre) explanations of disengagement. It concentrates on the latter and, accordingly, builds on critical, post-Marxist and elite-oriented work. As such it follows on from earlier calls in the journal for a return to elite-based research ( Savage and Williams, 2008). Drawing on general concepts in economic sociology ( Polanyi, Granovetter) the article presents an alternative embedding-disembedding paradigm for explaining and evaluating this tendency towards political elite disengagement. The propensity for politicians to disembed from wider society is explained by way of a series of eight 'filters'. Such filters work, alone or cumulatively, both to socially embed political elites within the institutions and networks of formal politics and also to disembed them from wider society and the populace they represent. The interpretive framework outlined here draws on a combination of secondary literature and ongoing interview-based research with some 150 political actors (politicians, journalists, officials) working at Westminster. As such, the filters and embedding-disembedding paradigm focuses primarily on the UK case. However, the framework is easily adaptable to other nations and systems.
Sociology
Keywords: Great Britain - politics & government; communication; disengagement; elite (social sciences); embedding/disembedding; organizations; political communication; political elites; political organizations; political participation laws; politicians

The New ‘Passive Revolution’ of the Green Economy and Growth Discourse: Maintaining the ‘Sustainable Development’ of Neoliberal Capitalism - Wanner, Thomas (New Political Economy, 2015)
This paper analyses the rapidly emerging discourse of a green economy based on green growth. It highlights inherent conflicts and contradictions of this discourse such as the myth of decoupling growth from the environment, pollution generations and resource consumption. Using key theoretical constructs of both Gramsci and Polanyi, the paper argues that the green economy/growth discourse can be seen as a Gramscian ‘passive revolution’ whereby the dominant sustainable development discourse, subsumed by capitalist hegemony, is protected in the context of global environmental, economic and development crises. The ‘neoliberalising of nature’, or in other words, the privatisation, marketisation and commodification of nature, akin to Polanyi's fictitious commodities, continues and intensifies with green economy/growth strategies. Greening the economy and associated strategies of green growth divert attention from the social and political dimensions of sustainability and issues of social and international justice. In this way, the inexorable march or ‘sustainable development’ of neoliberal capitalism is maintained. This paper goes on to argue that contesting the claims of green economy/growth discourse through political struggles by civil society against the neoliberalisation of nature is a sign of a slowly emerging counter-hegemonic ‘double movement’ which challenges capitalist hegemony and the commodification of society–nature relations.
Geography
Keywords: GRAMSCI; Antonio; 1891-1937; environmental economics; fictitious commodities; green economy; green growth; neoliberalising nature; neoliberalism; passive revolution; privatization; research; social justice - environmental aspects; sustainable development

Facing an unequal world - Burawoy, Michael (Current Sociology, 2015)
To face an unequal world requires us to interpret and explain it, to be sure, but also to engage it, that is, to recognize that we are part of it and that we are partly responsible for it. In other words, inequality is not just something external to us, but also invades our own world. I begin, therefore, by examining the global community of sociology through the lens of inequality. I then consider two recent perspectives on our unequal world from outside sociology: the moral radicalism of Pope Francis that emphasizes exclusion from market society, and the innovative research of the economist Thomas Piketty that emphasizes unequal inclusion in market society. These two faces of global inequality mirror the social movements reverberating from the economic crisis of 2008 but which have their roots in a reaction to a broader wave of marketization, the third to engulf modern capitalism. To explore the meaning of third-wave marketization, otherwise known as neoliberalism, and the social movements it provokes I draw on two concepts from Karl Polanyi – ‘fictitious commodities’ and ‘countermovement’ – as well as a theory of the dynamics of capitalism. I conclude with three challenges facing a global sociology that centers social movements: to develop a theory that speaks to the globally diverse experiences of commodification; to develop a methodology that recognizes that we are unavoidably participants in the world we study; and to develop a politics that defends a particular vision of that world, a vision that has defined the sociological tradition from its beginning, namely one that upholds the centrality of civil society against the over-extension of market and state.
Sociology
Keywords: globalization; inequality; markets; social movements; sociology

Reforming States, Agricultural Transformation, and Economic Development in Russia and Japan, 1853-1913 - Cohen, Mark (Conference Papers – American Sociological Association, 2015)
Capitalist economic development has occurred unevenly, as certain economies began sustained growth relatively early, opening up an increasingly large gap with lagging countries. This well-known fact has encouraged much research on the prospects for undeveloped economies to "catch up" to the earlier developers. Japan and Russia in the late nineteenth century were two of the first countries outside of western Europe to experience substantial catch-up growth. Beginning in the 1860s, political elites in both countries adopted wide-ranging reforms in pursuit of military modernization and its political and economic prerequisites. This paper analyzes the impact of the two states' reform programs on their countries' rural economies, which represented the vast majority of population and production. Adopting a Polanyian perspective on economic development, this paper finds that only in Japan were agrarian relations transformed so as to set off a process of capitalist economic development centered on rural areas. This divergence is explained by the different stances of the two reforming states towards landlords and peasant communities.
Sociology
Keywords: Japan; Russia; economic development; rural economies

Karl Polanyi's Environmental Sociology - Fenner, Weston Henry, IV; Brechin, Steven R. (Conference Papers – American Sociological Association, 2015)
Drawing upon The Great Transformation (1944), we outline Karl Polanyi's environmental sociology by presenting his major insights on economic substantivism, fictitious commodities, and double movements. Polanyi wrote his opus in challenge to Von Mises' Austrian School of Economics and its pursuit of an autonomous, self-regulating global free market. Polanyi's recognized the social and environmental limits of a fully free market and reasoned that inevitable market excesses would result in the rise of society self-protection to preserve land along with labor and money. We believe Polanyi's insights make him an important classical contributor to environmental sociology on par with Robert Malthus, Karl Marx, Max Weber, and Emile Durkheim. We conclude by outlining possible connections to established environmental sociology theories and literatures.
Sociology
Keywords: double movement; double movements; economic substantivism; environmental sociology; fictitious commodities; market fundamentalism; social theory

Denaturalizing the Market: Primitive Accumulation, Class Reformation, and the Rise of Colombia's Anti-Neoliberal Countermovement - Hough, Phillip A. (Conference Papers – American Sociological Association, 2015)
This paper addresses what labor movement scholars are calling the "Polanyi-problem" - how societal movements can effectively re-embed neoliberal markets back into society - by drawing upon recent interpretations of Karl Marx writings on primitive accumulation and class formation. The author focuses on the case of Colombia's coffee farmers (cafeteros) - a class of producers whose historically-privileged modality of class reproduction was undermined by the liberalization of the coffee market in the 1990s and who have engaged in two major waves of protest aimed at re-embedding the coffee market back into society (1993-2001; 2013-2014). While similar in terms of movement targets, tactics, and general goals, a significant shift has occurred in the cafeteros' demands which is reflective of a fundamental transformation of their class identity away from one that 'naturalized' their dependence upon the coffee market to meet their subsistence needs and towards one that 'de-naturalizes' their dependence upon this market. This 'denaturalizatization of the market' undermined their ability to mobilize around a privileged form of class identity. Yet, it provided them with the ability to generalize their struggle beyond the confines of the coffee economy and therefore develop into a broad, national anti-neoliberal agrarian Polanyian counter-movement.
Sociology
Keywords: Colombia; Polanyi problem; countermovement; primitive accumulation; reembedding

Challenging Dominant Market Theories in Five Ways[1] - Janoski, Thomas (disClosure, 2015)
This article discusses why many social scientists including Karl Polanyi, Max Weber, and Karl Marx are dissatisfied with an overreliance on markets, and a conceptualization of markets being efficient, fair and rational. Topics include five types of arguments critical of markets including the Marxian approach to markets, the rise of Karl Polanyi's view that markets are fragile, and a more complex decision-making approach starting with Max Weber's view of social action.
Sociology
Keywords: MARX; Karl; 1818-1883; WEBER; Max; 1864-1920; markets; social action; social scientists

Toward a Sartrean Economics - Kail, Michel; Sobel, Richard (Rethinking Marxism, 2015)
Despite the absence of a systematic analysis of economics in Sartre's work, we argue that a Sartrean economics can indeed be said to exist, even if it is an economics that still awaits development. The status that Sartre accords to the concept of scarcity allows him to advance the critique of economism begun by Karl Polanyi, who, for his part, had been satisfied simply to challenge the reduction of economics to its formal definition. Scarcity, Sartre teaches us, should not be submitted to the process of instrumental reason but should be considered as a fact of human history. Economic analysis, meanwhile, should not be based solely on the theme of man's confrontation with a typically ungrateful nature but should rather be articulated through the concept of the world as elaborated in Sartrean philosophy.
Political Science; Philosophy
Keywords: POLANYI; Karl; 1886-1964; SARTRE; Jean-Paul; 1905-1980; economic systems; economism; scarcity; world

The Limits of Transformation: Contemporary Applications of Karl Polanyi - England, Christopher (Journal of Australian Political Economy. Summer2015/16, Issue 76, 2015)
The article explores the conception of the Great Transformation (GT) by economic historian Karl Polanyi and its contemporary applications. Topics covered include the continued existence of free market fundamentalism as a prominent ideology and as a living political project, the persistence of free market utopianism, and Polanyi's genealogy of the market system. Also discussed are his conception of industrialism and his use of functionalist theory to build a unified image of the social system.
Political Science
Keywords: economics; free enterprise; functionalism; industrialism; political economy; social systems; utopias

A Reversed Double Movement in Brazil: The (Controversial) Evolution of the Partido dos Trabalhadores' Education Policy since 1980 - Guedes-Neto, Joao Victor (Journal of International Studies, 2015)
Karl Polanyi identified a double movement which took place during the bourgeoisie hegemony when, instead of liberalism, it has made use of interventionism to perpetuate its domination over the working class. Several studies have tried to update his analysis by identifying the double movement nowadays. Nevertheless, the academia has not addressed the possibility of a reversed phenomenon where the working class would make use of liberalism to perpetuate itself in power. This paper aims at analyzing the Brazilian case where the Partido dos Trabalhadores, a proxy for the working class, has implemented pro-market policies in higher education. Whereas the party has not passed through structural reforms such as the British and German working class parties, it has drastically changed its approach to policy-making and campaigning since its origin in 1980. The study concludes that a reversed double movement may occur when the working class is in charge of the government.
Political Science; International Relations
Keywords: double movement; economic development; education; education: government policy; human development; human resources; income distribution; migration; national government expenditures and education

Law, Fugitive Capital and Karl Polanyi's the Great Transformation - Kendall, Walter J. III (Indonesian Journal of International & Comparative Law, 2015)
Law
Keywords: embeddedness; law and economics; law and society; legal philosophy; legal reform; liberalism

Critique and transformation: On the hypothetical nature of ecosystem service value and its neo-Marxist, liberal and pragmatist criticisms - Melathopoulos, Andony; Stoner, Alexander (Ecological Economics, 2015)
Ecosystem service valuation (ESV) attempts to transform the opposition of human economic necessity and ecological conservation by valuing the latter in terms of the services rendered by the former. However, despite a number of ESV-inspired sustainability initiatives since the 1990s, global ecological degradation continues to accelerate. This suggests that ESV has fallen far short of its goals of sustainable social transformation—a failure which has generated considerable criticism. This paper reviews three prominent lines of ESV criticism: 1) the neo-Marxist criticism, which emphasizes the “fictitious” character of ecosystem commodities; 2) the liberal criticism through Friedrich Hayek's concept “scientistic objectivism”; and 3) the pragmatist criticism of “value monism”. Although each form of criticism provides insight into the limitations of ESV, all share ESV's inability to discern what kind of social transformation is possible . Unable to provide an account of their own immersion in social and historical context, these approaches operate in the hypothetical . In light of these shortcomings, this paper advances a critical theory approach, which we contend provides conceptual tools uniquely well-suited to more adequately address the question of social transformation.
Economics
Keywords: Marxian economics; ecosystem services; neoliberalism; pragmatism; social development

Economics Humanized - Pearson, Dan (Issues in Science & Technology, 2015)
Science & Technology
Keywords: BLOCK; Fred L.; Power of Market Fundamentalism: Karl Polanyi's Critique; The (Book); SOMERS; Margaret R.; book review; economics; nonfiction; science and technology

Contesting 'Actually Existing' Neoliberalism - Ryan, Matthew (Journal of Australian Political Economy, 2015)
The article explores the established conception of actually existing neoliberalism. Topics covered include free-market neoliberalism, the nature of neoliberal theory, and the distinction between esoteric and exoteric neoliberalisms. Also discussed are the ideas of scholars Karl Polanyi and Ha-Joon Chang about the role of the state in capitalist development, and scholar Damien Cahill's idea that neoliberalism is defined by microeconomic policies of privatization, marketization and deregulation.
Political Science
Keywords: CAHILL; Damien; CHANG; Ha-Joon; esotericism; free enterprise; neoliberalism; political economy